Growth and morphology of captive female Common Eider Somateria mollissima ducklings - Hawkins, Penny A J; Butler, P J; Woakes, A J (Wildfowl, 1998)
Five female Common Eider ducklings taken under licence from a population at the Isle of May, Firth of Forth, Scotland, were reared from eggs. Weekly measurements were made of the tibiotarsus, ulna, head, ninth primary, body mass, wing and foot area. The body components attained adult size in the following order: tibiotarsus (six weeks), ulna (seven weeks), foot area (eight weeks), body mass and head (nine weeks), wing area and wing loading (ten weeks) and ninth primary (eleven weeks). Paddle index (the ratio of foot area to body mass) remained relatively constant throughout development. Up to and including seven weeks old, body mass could be used as an estimate of age according to the relationship A= 0.005 M(B) + 0.015, where A = age (weeks) and M(B) = body mass (g) (R^2 = 0.98). Feathering up' began by the second week and was completed during weeks seven to eight. There was no noticeable trough in the body mass curve when the ducks fledged at nine to 10 weeks.